1987
DOI: 10.1111/j.1365-2141.1987.tb06171.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced erythrocyte survival following clearance of malarial parasitaemia in Thai patients

Abstract: Erythrocyte survival times were measured in healthy Thai controls and in patients following clearance of asexual P. falciparum or P. vivax parasitaemia. In five controls the mean cell life (MCL) of compatible donor erythrocytes was 89.6 d (mean range 73-101 d) compared with a mean MCL of 56.8 d (range 30-66 d) for autologous erythrocytes in 12 falciparum patients. In one of these patients the survival curve was biphasic with a rapid loss of some labelled cells. The survival of compatible donor erythrocytes was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
68
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 23 publications
4
68
0
Order By: Relevance
“…Full supportive care was given as described previously. 3 A control group of 22 healthy age-and sexmatched Thai volunteers provided a blood sample for measurement of RBC deformability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full supportive care was given as described previously. 3 A control group of 22 healthy age-and sexmatched Thai volunteers provided a blood sample for measurement of RBC deformability.…”
Section: Methodsmentioning
confidence: 99%
“…It is thought to result from a combination of parasitized erythrocyte destruction at schizont rupture, accelerated removal of both parasitized and unparasitized red blood cells, and ineffective erythropoiesis. [3][4][5][6] Of these factors, removal of unparasitized red blood cells is the most important, accounting for approximately 90% of the reduction in hematocrit in acute malaria (Price R and others, unpublished data). We have shown previously that the threshold for splenic removal of heat-damaged or antibody-coated erythrocytes in acute malaria is lowered, suggesting enhancement of both mechanical filtrative function and Fc receptor-mediated clearance.…”
mentioning
confidence: 99%
“…Rheological changes are likely to contribute to splenic sequestration of parasitized red cells. Looareesuwan et al (9) have suggested that P. falciparum and P. uivax infections may lead to increased destruction of unparasitized red cells. Red cell changes, in theory, may result from the direct and indirect effects of the parasite on the red cell as well as the pathophysiological response of the patient.…”
mentioning
confidence: 99%
“…Anemia is caused partly by the loss of red blood cells, both infected erythrocytes (IEs) and uninfected erythrocytes (UEs), which are destroyed by hemolysis or phagocytosis. 3 Rigidification of the membranes of IEs and UEs during infection may be an important factor in the destruction of these cells during passage through the spleen. 4,5 There seem to be many causes of anemia, and the underlying mechanisms remain elusive.…”
mentioning
confidence: 99%